Design and Implementation of 1-2 GHz Stepped Frequency GPR for Buried Metal Detection - Suryana, Joko; Suksmono, Andriyan B.; Mengko, Tati R. (UI Scholars Hub, 2005)
Design and Implementation of 1-2 GHz Stepped Frequency GPR for Buried Metal Detection. In this paper, we describe the design and realization steps of 1 – 2 GHz SFGPR (Stepped Frequency Ground Penetrating Radar) transceiver for metal detection under the ground. Before using prototyped GPR for detecting the metal under the ground, several of calibration processes must be performed, namely phase calibration and monocycle pulse waveform calibration. After completing the calibrations, this prototyped GPR would be ready for detecting a hidden object such as a metal plate 5 cm under the ground in our small test range size 25 cm x 75 cm x 10 cm. From the calibration and detection results, we concluded that the prototyped SFGPR passed the technical specifications of the design and could perform the metal detection under the ground with high SNR.